On admissions, access and the beginning of university in Argentina. A study through time. (Praxis Educativa, 2025)
This article explores the evolution of the concepts of admission, access, and beginnings in Argentinian universities, within the context of the expansion of the higher education system. Through an analysis of educational policies, institutional actions, and researchers' perspectives, it shows how the conceptualization of admission has shifted from a vision of class and exclusion to one of right and democratization. The study highlights the emergence of the concept of "beginnings" as a new approach that integrates the pedagogical, social, and cultural dimensions of the transition to university life.